Bear Creek V. Peru and the Legality of the Investment as a (Implied) Requirement for the Investment Arbitration Tribunal’s Exercise of Jurisdiction - Talavera Cano, Andrés (2020)
Concerns about inconsistency in the application of standards in arbitral awards are strongly present in investment treaty arbitration. In particular, tribunals can regularly exercise a varying scope of jurisdiction when they determine the legality requirement that demands foreign investments to be made in accordance with the law of the host state.In this paper, the author seeks to analyze the decision rendered by the tribunal in Bear Creek v. Peru, in which the Canadian mining company alleged that the Peruvian State breach, inter alia, expropriation protections under the Canada-Peru Free Trade Agreement in relation to its investment in the silver mining project of Santa Ana. In order to achieve this aim, in the first chapter, he addresses three key issues regarding the tribunal’s jurisdiction, the rights on which the company based its claim and the arguably prerequisite of legality or good faith for the tribunal’s exercise of jurisdiction. In the second chapter, he analyzes the validity of the tribunal’s interpretation on the legality requirement for investment as an implicit element in the relevant treaty to determine the tribunal’s jurisdiction.